Identifikasi Cacing Dan Telur Cacing Pada Sayuran Lalapan Di Pasar Tradisional Kota Semarang - Ana Yustika; Aprin Wijayanti; Seno Ari Tjahjo P (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Vegetables are an important type of food for humans. Lack of vegetable consumption can increase the risk of developing degenerative diseases such as obesity, coronary heart disease, kidney failure, diabetes, hypertension, and cancer. Fresh vegetables are vegetables that are usually served raw, so it is estimated that they are the source of Soil-Transmitted Helminth (STH) infection in humans. Some examples of fresh vegetables include cabbage, lettuce, basil, leeks, celery, and mustard greens. The purpose of this study was to determine the results of the identification of worm eggs and adult worms in fresh vegetables sold in traditional markets in Semarang City. This type of research is called descriptive qualitative research. The subjects of this study were all fresh vegetables sold in the traditional markets of Semarang City. The research sample was taken by random sampling from all areas of Semarang City, covering the areas of Central Semarang (Johar Market), North Semarang (Purwogondo Market), East Semarang (Langgar Indah Market), West Semarang (Karang Ayu Market), and Semarang South (Peterongan Market). The results showed that the vegetables sold in the Peterongan Market and Purwogondo Market were not found to be contaminated. Meanwhile, fresh vegetables sold at Langgar Market, Johar Market, and Karang Ayu Market were found to be contaminated. Contamination that occurs in fresh vegetables in the traditional market of Semarang City is caused by Oxyuris vermicularis worm eggs, hookworm eggs, Ascaris lumbricoides worm eggs, hookworm larvae, and adult hookworms.